2015
DOI: 10.1364/ao.54.001302
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic anisotropy of acoustooptic Tl_3AsS_4 crystals

Abstract: We present comprehensive experimental measurements and analysis of anisotropy of the acoustic wave velocities for TI(3)AsS(4) crystals, including the obliquity and nonorthogonality of the acoustic waves, and the deviations from purely longitudinal and transverse polarization types. We have found that the crystals under analysis are characterized by rather low transverse wave velocities v(23) and v(32), which are both equal to 630 m/s. It is shown that the efficiency of acoustooptic (AO) interactions in TI(3)As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…These figures are comparable with those typical for the best acoustooptic materials (e.g., TeO 2 crystals [8]). Moreover, as shown in our recent work concerned with the acoustic anisotropy [9], the efficiency of the acoustooptic effect in Tl 3 AsS 4 can become even higher if the anisotropic interaction of optical wave with the slowest transverse acoustic wave is provided. Under such conditions, the acoustooptic figure of merit can become extremely high (~ 12 3 3 10 s /kg   ).…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…These figures are comparable with those typical for the best acoustooptic materials (e.g., TeO 2 crystals [8]). Moreover, as shown in our recent work concerned with the acoustic anisotropy [9], the efficiency of the acoustooptic effect in Tl 3 AsS 4 can become even higher if the anisotropic interaction of optical wave with the slowest transverse acoustic wave is provided. Under such conditions, the acoustooptic figure of merit can become extremely high (~ 12 3 3 10 s /kg   ).…”
Section: Introductionmentioning
confidence: 75%
“…At the room temperature and the light wavelength of 632.8 nm   , the plane containing the optic axes coincides with the crystallographic plane ab, where the b axis represents the acute bisector of the angle 2V between the optic axes (2V = 28.46 0.1 deg  ) [9]. The Faraday rotation becomes free of accompanying optical effects whenever the light propagates along one of the optic axes and the magnetic field is applied in this direction.…”
Section: Experimental Conditions and Proceduresmentioning
confidence: 99%
“…The same concerns the EOCs, of which modules belong to the region of 0.28-0.54. We have also shown [8] Notice that the other geometries of AO interactions, even those at which the acoustic waves propagate along the principal crystallographic axes, have not yet been scrutinized. The only exception is the work [2] where the absolute values of several EOCs and the corresponding AOFMs have been determined for the case of isotropic diffraction.…”
Section: Introductionmentioning
confidence: 97%
“…Moreover, Tl 3 AsS 4 is a promising material for thermal imaging [6]. Recently, we have determined the complete matrices of piezooptic and elastooptic coefficients (EOCs) [7] for the Tl 3 AsS 4 crystals, together with the complete matrices of elastic stiffness and compliance coefficients [8]. It has been found that the piezooptic coefficients are very high, being 10 -11 N/m 2 in the order of magnitude.…”
Section: Introductionmentioning
confidence: 99%
“…As is known, crystals of triple chalcogenides, as well as TI3AsS4, are used as elements of acousto-optical filters operating in the infrared region of the spectrum [4]. Despite the unique acousto-optical properties in the infrared range of the spectrum, single crystals of ternary thallium chalcogenides Tl3AsSe3, Tl3AsS4, Tl3PSe4, Tl3VS4, TlGaSe2, TlGaS2, TlInSe2, Tl3TaS4 and Tl3TaS4 have not been sufficiently studied.…”
Section: Introductionmentioning
confidence: 99%